Approach to the assessment of the financial and accounting risks with digital economy conditions for projects (representation) - Alkarawy, Heyder G. Wannes; Al-Sultani, Mohammed Madlool; Adnan, Hind; Al-Ssadi, Nasser Jassem Nasser; Abedi, Ahmed Abd Zaid (The journal of contemporary issues in business and government, 2021)
The digitization of the economy in the modern world has become an inevitable process that objectively affects all areas of society and determines the direction of its development. The importance of the study is evidenced by the high degree of modern development combined with the constant transformation. In the process of informing the economy, the implementation of the principles of digitizing the economy by an organization is impossible without the use of tools that can ensure the continuous work on making changes to the current economic system. These tools are (acting) projects. Which called for classifying projects (representation) into the five groups. The numerical procedures for project risk (representation) are defined from three scenarios in which each scenario and its risks are identified. The evaluation of the assessed factors of the digital (representation) project was developed on a scale of 3 weight points for each risk, as well as calculating the importance of risks regarding the not optimal level for a fraction of the cost of the project and Implementing (feasibility) the project in decision-making of choose the project (representation) or Non-continuity of the project (representation) during implementation. Which indicates the importance and importance of this risk to the project and to the financial stability of the company as a whole.